Connectivity of claw-free maximal nontraceable graphs - Dunbar, Jean E.; Harris, John M.; Frick, Marietjie; Van Aardt, Susan (Utilitas Mathematica, 2011)
It is known that there exists a 2-connected claw-free maximal nontraceable graph of order n for every n ≥ 18. We demonstrate the existence of a 3-connected claw-free maximal nontraceable graph of order n for every n ≥ 60.